Flow structures in wake of a pile-supported horizontal axis tidal stream turbine. (March 2020) - Zhang, Jisheng; Lin, Xiangfeng; Wang, Risheng; Guo, Yakun; Zhang, Can; Zhang, Yuquan
Abstract: This study presents results from laboratory experiments to investigate the wake structure in the lee side of a scaled three-bladed horizontal axis tidal stream turbine with a mono-pile support structure. Experiments are conducted for a range of approaching flow velocity and installation height of rotor. Analysis of the results shows that bed shear stress increases with the increase of approaching velocity and decrease of installation height within 2 D ( D is the diameter of the rotor) downstream of the rotor. The flow field within 2 D downstream of the rotor is greatly influenced by the presence of nacelle and mono-pile. Low stream-wise flow velocity and large turbulence intensity level is detected along the flume center right behind the nacelle and mono-pile from 1 D to 2 D downstream of the rotor. Stream-wise velocity at the blade tip height lower than the nacelle increases sharply from 1 D to 2 D and gradually grows afterwards. Correspondingly, the turbulence intensity decreases quickly from 1 D to 2 D and slowly afterwards. Large bed shear stress is measured from 1 D to 2 D, which is closely related to turbulence induced by the mono-pile. It is also found that the presence of the mono-pile might make the flow field more 'disc-shaped'. Highlights: Bed shear stress is greatly affected by the presence of the mono pile. . Velocity recovers quickly within two diameter downstream and slowly afterwards. Turbulence intensity declines significantly within two diameter downstream and gradually afterwards. The mono pile might make the turbulence field more 'disc-shaped'.